Abdominal Cerebrospinal Fluid Pseudocyst Diagnosed by Point-of-Care Ultrasound. Issue 6 (June 2016) - Ivan, Yaron; Marin, Jennifer; Hauptman, Jason
Abstract : Abstract: Abdominal cerebrospinal fluid pseudocyst is an uncommon complication of ventriculoperitoneal shunt and is seen more commonly in the pediatric population. The diagnosis of an abdominal cerebrospinal fluid pseudocyst is typically made by ultrasonography, which demonstrates a simple or loculated fluid collection in the abdomen. We present a case of abdominal pseudocyst diagnosed by point-of-care ultrasound.